Experimental investigation and effective medium approximation of thermal conductivity of water based exfoliated Graphene nanofluids - Arifutzzaman, A. K. H. A. Ma; Ismail, Ahmad Faris; Yaacob, Iskandar Idris; Khan, Ahsan Ali; Alam, Md. Zahangir (Research India Publications, 2018)
In this work Graphene (Gr) flake was exfoliated using the solvents N-Methyl-2-Pyrrolidone (NMP) and processed by systematic centrifugation. Raman spectroscopy and Field Emission Scanning Electron Microscopy (FESEM) analysis were conducted for the characterization of as fabricated Gr flakes. Exfoliated Gr was re-dispersed into the deionized water (DW) with the aid of vacuum filtration process. Then five different nanofluid samples were prepared by dispersing Gr in DW (Gr/DW). In these samples volume fractions of Gr were varied from 0.10 to 0.30 % in DW. Systematic thermal conductivity (TC) measurements were conducted separately on the prepared Gr dispersed nanofluid samples. Prediction of TC enhancements for Gr/DW nanofluids were explained by analytical explanation with the modification of effective medium approach (EMA). In the approximation low filling of Gr flake and its random orientation were taken into consideration with the effect of ultrathin Gr fake’s basal plane TC. The model predictions agreed very well with the measured TCs of as produced exfoliated Gr/DW nanofluids. It was shown that, using exfoliated Gr flakes of extremely wide basal plane with negligible thickness and non-flat or crumpled ratio was an efficient factor to obtain the considerably better agreement with the TC enhancements of Gr/DW nanofluids.